2018
DOI: 10.3233/jad-189011
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis, Hypertension, and Diabetes in Alzheimer’s Disease, Vascular dementia, and Mixed Dementia: Prevalence and Presentation

Abstract: On page 1253, the right column, line 6 from the bottom, the text gives [58] as a reference: "In 2013, the prevalence of DM was reported to be 15.6% among the normal Swedish population in individuals >65 years [58], which is an age group in proximity to our study group (81 years, SD 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Furthermore, it is also possible that the two cognitive domains identified in the present study, executive function and explicit memory, are reflective of two pathways in which metabolic risk factors may affect mobility. Dementia is a disease that affects memory, language, planning, and problemsolving, and most prevalent subtypes of dementia are Alzheimer's disease and vascular dementia (Javanshiri et al, 2018). While Alzheimer's disease is neuropathologically defined as the presence of amyloid plaques and accumulation of neurofibrillary tangles composed of filamentous tau protein (Perl, 2010), vascular dementia is a cognitive disorder that is derived from cerebrovascular cases (Iadecola, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is also possible that the two cognitive domains identified in the present study, executive function and explicit memory, are reflective of two pathways in which metabolic risk factors may affect mobility. Dementia is a disease that affects memory, language, planning, and problemsolving, and most prevalent subtypes of dementia are Alzheimer's disease and vascular dementia (Javanshiri et al, 2018). While Alzheimer's disease is neuropathologically defined as the presence of amyloid plaques and accumulation of neurofibrillary tangles composed of filamentous tau protein (Perl, 2010), vascular dementia is a cognitive disorder that is derived from cerebrovascular cases (Iadecola, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, cardiovascular disease, cerebrovascular disease, atherosclerosis, hypertension, diabetes mellitus, and stroke were considered risk factors for developing vascular dementia (Song, Lee, Park, & Lee, 2014). However, recent evidence suggests that these risk factors are also common in Alzheimer's disease (Javanshiri et al, 2018); thus, cardiometabolic abnormalities may impact both dementia subtypes. While Alzheimer's disease is commonly associated with impaired explicit memory (Bondi & Kaszniak, 1991), executive dysfunction is associated with both Alzheimer's disease and vascular dementia (McGuinness, Barrett, Craig, Lawson, & Passmore, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dementia (VD) is a type of cognitive impairment contributed by cerebrovascular disease, whose clinical manifestations are memory decline, early gait disorder, incontinence with mood (e.g., depression and apathy), and personality changes (Habeych and Castilla-Puentes, 2015). The WHO estimates there will be about 82 million people with dementia in 2050, twice as many as now (Javanshiri et al, 2018). VD is a fatal subtype of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…According to an experiment by Chen et al, vegetarians with a lower risk of AS also had a lower incidence of cognitive impairment (Chen et al, 2018), which reflects the relationship between blood vessels and cognition, allowing further hypothesis about AS playing a role in VD. Prior trials have shown that AS has a significant influence on VD (Chen et al, 2018;Javanshiri et al, 2018). There are currently two theories about their relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological control of blood pressure may reduce dementia incidence 8 . However, not all studies show a link between high blood pressure and Alzheimer's disease forms of dementia 13 , and it is noted that blood pressure decreases with age 14 . The exact mechanism by which hypertension increases dementia risk is not yet clear, but it is thought that hypertension may contribute to vascular dementia via cerebrovasculature damage 15,16 .…”
mentioning
confidence: 99%